(untitled) (Carte Romanze, 2020)
The manuscript Latin 5564 of the Bibliothèque Nationale of Paris is a monastic recueil belonged to the library of the Abbey of Saint Martial in Limoges. In the last leaves of this manuscript I found an early thirteenth-century transcription of few verses of the well-known Provençal religious poem Mei amic e mei fiel, also included in the ms. BnF, Latin 1139. Among the variants which characterize the recovered verses compared to the text of ms. latin 1139, the most important is the word masan ‘noise, confusion’, which replaces gazel, the famous and enigmatic hapax legomenon whose real meaning could be shown by the comparison with the meaning of masan.